Flow of a Jeffrey Fluid Between Two Long Vertical Thin Plates with Porous Medium - Sreenadh, S.; Govindarajulu, B.; N.S. Srinivas, A.; Nageshwar Rao, R. (International Journal of Engineering and Technology, 2018)
The present study investigates fully developed free - convection Jeffrey fluid flow between two vertical plates with porous medium. The vertical plates are moving with same velocity but in opposite directions. The coupled nonlinear governing equations are solved by using the linearization technique. The solutions for velocity distribution, temperature distribution, skin friction and rate of heat transfer is obtained in the presence of porous medium by Iterative procedure.Â  Shooting technique with Runge - Kutta method of order four is proposed to compare the numerical results for velocity and temperature distribution. The numerical results obtained by both methods are compared and presented graphically. It is observed that an increase in the permeability parameter causes decrease in the fluid velocity and an increase in the Jeffrey fluid parameter causes an enhancement in the fluid velocity. The significance of various pertinent parameters like Grashof number, Prandtl number, Eckert number and the plate velocity are explained through graphs.Â Â